Enhancement Activities for the Day Care Centers and Development Workers - Cadosales, Maria Nancy Q. (JPAIR Multidisciplinary Research, 2011)
Day Care Centers are managed by Day Care Workers (DCWs). These teachers contribute to the total development of the early childhood learners. In this present study, it was noted during the interview and focus group discussion that the DCWs needed enhancement activities for them to carry out their teaching tasks. Exercises on letter sound were the most priority need over teaching strategies, production of instructional materials, and pedagogy. Thus, an action plan for a three-day enhancement program was proposed.
Keywords: Day Care Centers; Day Care Workers (DCWs); Early childhood learners; Enhancement activities; Letter sound exercises